Characterization of wrapping and coating techniques for light-reflecting materials of LaBr3(Ce) scintillation detector - R. A. El-Tayebany (Scientific Reports)
Abstract Scintillation detectors need materials that reflect light in order to detect the incident photons or charged particles. It is necessary to attain an extremely high light accumulating efficiency. The purpose of this study is to investigate how coating and wrapping reflective materials which are employed to maximize light collection affect scintillator output. The MCNPX code was used for the simulation of the setup including LaBr3:Ce with the default reflector. The scintillators’ spectrum responses were evaluated with 235U, 238U, and 137Cs included. All the outcomes were discussed and explicated.